(untitled) (Annals of Medical Research, 2021)
Aim: In this study we compared outcome of antegrade and retrograde radical prostatectomy with new homeostasis devices.Material and Methods: Present study includes retrograde view of prospective recorded data between January 2006 and January 2016 in two different centers.The antegrade technique was applied to 67 cases with the Thunderbeat and the retrograde technique was performed as described by Reiner and Walsh before include with early division of the urethra.Demographic data,operative data (tPSA, ISUP, DM, etc.) and post-operative data (transfusion, hospitalization, surgical margin positivity, stenosis, etc.) were evaluated.Results: There was no difference in terms of demographic status.Incontinence resolved in 29patients in the antegrade group(%43) and resolved in 32patients in the retrograde group(%64) (p=0.012). Erectile dysfunction was observed in 28 patients in the first group(41%) and in 18 patients in the second group(36%) (p=0,359).There was a statistical difference in terms of surgical margin positivity in favor of the antegrade group for these results(p=0.003). Transfusion was required by 11 patients (16%) with the antegrade technique and in 9 patients (18%) with the retrograde technique (p=0.055).There was no difference in terms of anastomosis stenosis and operation duration (p=0.357 and p=0.108).Conclusion: In our study,the antegrade method was shown to be an easier method with less hemorrhage,more reliable preservation of the neurovascular bundle and adding Thunderbeat to the procedure was found to add to the ease of surgery.